1987
DOI: 10.1080/00222895.1987.10735402
|View full text |Cite
|
Sign up to set email alerts
|

Force Control and Its Relation to Timing

Abstract: Previous work (Keele & Hawkins, 1982; Keele, Pokorny, Corcos, & Ivry, 1985) has suggested two general factors of coordination that differentiate people across a variety of motor movements, factors of timing and maximum rate of successive movements. This study provides comparable evidence for a third general factor of coordination, that of force control. Subjects who exhibit low variability in reproducing a target force with one effector, the finger, tend to show low variability with two other effectors, the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 9 publications
7
51
1
Order By: Relevance
“…On the other hand, observations of changes in movement frequency at the same time as preservation of force profiles, or vice versa, during stereotyped rhythmic movement have been observed before (Hansen et al, 2014;Sardroodian et al, 2016). Furthermore, Sternad et al (2000) also reported that force and frequency in rhythmic uni-manual tapping were largely independent (Sternad et al, 2000), in line with other previous observations (Keele, Ivry, & Pokorny, 1987), as well as the present observations. If stereotyped rhythmic movements, including tapping, are CPG-mediated, and CPGs are organised in two components; one responsible for rhythmic movement frequency and another responsible for rhythmic movement pattern (Dominici et al, 2011;Kriellaars et al, 1994;McCrea & Rybak, 2008;Perret & Cabelguen, 1980), the present findings point at largely separate and independent control of kinematics (frequency and displacement) and force during finger tapping.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, observations of changes in movement frequency at the same time as preservation of force profiles, or vice versa, during stereotyped rhythmic movement have been observed before (Hansen et al, 2014;Sardroodian et al, 2016). Furthermore, Sternad et al (2000) also reported that force and frequency in rhythmic uni-manual tapping were largely independent (Sternad et al, 2000), in line with other previous observations (Keele, Ivry, & Pokorny, 1987), as well as the present observations. If stereotyped rhythmic movements, including tapping, are CPG-mediated, and CPGs are organised in two components; one responsible for rhythmic movement frequency and another responsible for rhythmic movement pattern (Dominici et al, 2011;Kriellaars et al, 1994;McCrea & Rybak, 2008;Perret & Cabelguen, 1980), the present findings point at largely separate and independent control of kinematics (frequency and displacement) and force during finger tapping.…”
Section: Discussionsupporting
confidence: 92%
“…One of the most popular methods of measuring response force is with electrical resistance strain gauges (Angel, 1973;Freund & Büdingen, 1978;Giray & Ulrich, 1993;Ivry, 1986;Kantowitz, 1973;Keele et al, 1987;Klemmer, 1957;Mattes, Ulrich, & Miller, 1997;Miller & Franz, 2005;Mordkoff, Miller, & Roch, 1996;Schäffer, Giray, & Ulrich, 1989;Schröter, 2006;Stahl & Rammsayer, 2004; An inexpensive and accurate method of measuring the force of responses in reaction time research…”
Section: Techniques For Measuring Response Forcementioning
confidence: 99%
“…Yet, even with a simple keypress, there can be variation in the force of responses to stimuli (Ulrich & Wing, 1991), termed response force. Response force is related physically to the speed of the response, 1 but can continue beyond switch closure and so vary independently of RT Giray & Ulrich, 1993;Haagh, Spijkers, van den Boogaart, & van Boxtel, 1987;Ivry, 1986;Keele, Ivry, & Pokorny, 1987;Schröter, 2006;Sommer, Leuthold, & Ulrich, 1994;van Boxtel, van den Boogaart, & Brunia, 1993). Consequently, the importance of response force as a dependent measure lies not only in the confounding potential of response force in accurate interpretation of RT data Delabarre, Logan, & Reed, 1897;Ulrich & Wing, 1991;Woodworth, 1938), but also in the potential of response force to shed light on stimulusresponse conductance processes (Giray & Ulrich, 1993;Jaśkowski & Włodarczyk, 2006;Mattes, Ulrich, & Miller, 2002;Schröter, 2006;Stahl & Rammsayer, 2004;Ulrich, Rinkenauer, & Miller, 1998;Ulrich & Wing, 1991).…”
mentioning
confidence: 99%
“…Yet the contribution of 51% for the nonshared environment suggests that the external environment is important for its development. According to a modular approach of individual differences, general timekeeping ability seems to be a centrally organized function in the nervous system to account for the temporal aspects of movements (Jones, 1993;Keele, Ivry, & Pokorny, 1987;Keele, Pokorny, Corcos, & Ivry, 1985).…”
Section: Discussionmentioning
confidence: 99%